1999
DOI: 10.1359/jbmr.1999.14.7.1182
|View full text |Cite
|
Sign up to set email alerts
|

Oral Administration of the Growth Hormone Secretagogue MK-677 Increases Markers of Bone Turnover in Healthy and Functionally Impaired Elderly Adults

Abstract: Growth hormone (GH) stimulates osteoblasts in vitro and increases bone turnover and stimulates osteoblast activity when given to elderly subjects. Probably a major effect of GH on bone is mediated through stimulation of either circulating or locally produced insulin-like growth factor I (IGF-I). We determined the effect of chronic administration of the GH secretagogue, MK-677, on serum IGF-I and markers of bone turnover in 187 elderly adults (65 years or older) enrolled in three randomized, double-blind, place… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
13
0
3

Year Published

2001
2001
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(17 citation statements)
references
References 35 publications
1
13
0
3
Order By: Relevance
“…DG has been reported to be the "inactive" degradation product of AG but recent studies suggest that DG may itself have pleiotropic biologic activities, including opposing actions to AG (38)(39)(40)(41)(42)(43). In normal individuals, DG and AG levels decrease in parallel on feeding, but the ratio of DG/AG remains constant (22).…”
Section: Discussionmentioning
confidence: 99%
“…DG has been reported to be the "inactive" degradation product of AG but recent studies suggest that DG may itself have pleiotropic biologic activities, including opposing actions to AG (38)(39)(40)(41)(42)(43). In normal individuals, DG and AG levels decrease in parallel on feeding, but the ratio of DG/AG remains constant (22).…”
Section: Discussionmentioning
confidence: 99%
“…Chronic activation of the GHS-R by the small molecule agonist MK-0677 sustained rejuvenation of the GH/IGF-I axis in elderly subjects (25,38,(277)(278)(279)(280). This is accompanied by increased lean body mass and increased bone mass (38, [281][282][283]. In addition to beneficial effects on peripheral tissues, restoring young adult levels of GH and IGF-I is anticipated to be neuroprotective (213,284).…”
Section: A Identification Of the Ghs-r And Synthetic Agonistsmentioning
confidence: 99%
“…It is an analog of MK677, which was in clinical trials (11,16). It was dissolved in water and given to the mice daily by gavage.…”
Section: Compound Dosagementioning
confidence: 99%
“…Indeed, encouraging results from preclinical and clinical studies have indicated that GHS are efficacious in facilitating muscle development and mobilization in dogs whose hind legs were surgically immobilized (15). In a controlled clinical trial of elderly individuals, it improved the well being of the treated group (16). Markers of bone turnover were elevated in the 12-wk trial of these elderly people, suggesting that GHS will strengthen bones in the elderly.…”
mentioning
confidence: 99%